APPLYING MULTISENSORY APPROACH TO PROMOTE ENGAGEMENT IN PRIMARY ENGLISH HOME-BASED LEARNING - Novia Theresia; Michael Recard (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2021)
This paper introduces the multisensory approach as a way of teaching that promotes engagement by involving the learners’ senses of sight, hearing, touch, and physical movement. This paper aims to describe the teachers’ role in applying multisensory approach in Primary English Home-based learning, find the benefits and challenges in applying multisensory approach, and provide strategies to overcome the challenges. This study uses qualitative descriptive as the research method and the data was taken from the researcher’s reflections, lesson plans, observation reports and mentor’s feedback. This study shows that multisensory approach positively promoted engagement in primary English home-based learning. Several classroom activities that can be used in applying multisensory approach are Total Physical Response, color codes, storytelling, art & craft, and interactive PowerPoint. The challenges occurred from technicalities and monitoring the students’ behavior. Therefore, parents’ involvement is highly required to monitor students’ behavior in home-based learning process. For the next researcher, it is suggested to find ways to maximize home-based learning by maintaining social interaction among students.